The quality and reliability of short videos about premature ovarian failure on Bilibili and TikTok: Cross-sectional study - Ren Xu; Yanan Ren; Xinjun Li; Luyang Su; Jianzhi Su (Digital Health)
Background Premature ovarian failure (POF) is a condition where ovarian function ceases before age 40, leading to infertility and other health issues. As public health awareness increases, platforms like TikTok and Bilibili have become key sources for health-related content. However, the absence of peer review and regulatory oversight on short-video platforms may result in the spread of inaccurate or incomplete health information. This study evaluates the quality of videos related to POF on these platforms. Methods A cross-sectional study was conducted, analyzing 187 POF-related videos from TikTok and Bilibili. The modified DISCERN and Global Quality Score (GQS) assessment tools were used to evaluate video reliability and quality. Data on video characteristics, including engagement metrics and content, were also collected. Statistical analyses were performed to assess differences between platforms, video sources, and video quality. Result TikTok is more popular than Bilibili. Videos on both platforms related to POF had suboptimal quality, with TikTok's GQS median at 3 (2–3) and Bilibili's at 2 (1–3), showing a significant difference (p < 0.05). However, both had median modified DISCERN scores of 2 (1–3), with no significant difference (p > 0.05). On Bilibili, video duration was positively correlated with quality scores (p < 0.001), but no such correlation was found on TikTok. Symptoms of POF were the most common topic, with 29% of videos providing detailed explanations. Diagnosis and treatment were discussed in 16% and 7.4% of videos, respectively. Expert-uploaded videos demonstrated significantly higher quality than those from non-experts and personal users, with GQS and modified DISCERN scores of 3 (2–4) and 2 (1–3), respectively. Conclusions TikTok had higher engagement and better quality than Bilibili, but both platforms had inadequate video quality and reliability on POF. Expert videos were more reliable. These findings highlight the need for better regulation and monitoring of health content on short-video platforms.